2017
DOI: 10.1016/j.plefa.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a lipid-based nutrient supplement during pregnancy and lactation on maternal plasma fatty acid status and lipid profile: Results of two randomized controlled trials

Abstract: It is unknown whether a novel small-quantity lipid-based nutrient supplement (SQ-LNS) containing alpha-linolenic (ALA) and linoleic acids impacts maternal plasma lipids and fatty acid status. We measured plasma fatty acids (wt%) and lipid concentrations at 36 wk gestation and breast milk fatty acids (wt%) at 6 months postpartum in a subsample of women enrolled in a randomized controlled trial studying the effects of SQ-LNS on birth outcomes and child growth. Women≤20 wk gestation in Ghana (n=1,320) and Malawi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
2
11
1
Order By: Relevance
“…Previous studies in elderly adults have reported associations between Vitamin B12 status and verbal fluency (Bourre, ; Robins Wahlin, Wahlin, Winblad, & Backman, ). As stated above, no effects of LNS supplementation were found on breastmilk concentrations of DHA (Oaks et al, ), but breastmilk Vitamin B12 concentration was higher in both the LNS and MMN groups compared to IFA (Haber‐Donohue, personal communication). However, the associations of DHA and Vitamin B12 with executive function and working memory were independent of supplementation with LNS, because adjusting for intervention arm did not reduce the magnitude of these associations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies in elderly adults have reported associations between Vitamin B12 status and verbal fluency (Bourre, ; Robins Wahlin, Wahlin, Winblad, & Backman, ). As stated above, no effects of LNS supplementation were found on breastmilk concentrations of DHA (Oaks et al, ), but breastmilk Vitamin B12 concentration was higher in both the LNS and MMN groups compared to IFA (Haber‐Donohue, personal communication). However, the associations of DHA and Vitamin B12 with executive function and working memory were independent of supplementation with LNS, because adjusting for intervention arm did not reduce the magnitude of these associations.…”
Section: Discussionmentioning
confidence: 94%
“…Another potential explanation is that the higher amount of the omega‐6 fatty acid LA (4.6 g/day) compared to the omega‐3 fatty acid ALA (0.6 g/day) in LNS inhibited the synthesis of DHA (Harnack, Andersen, & Somoza, ), thus negatively affecting visuospatial performance. However, no effects of LNS supplementation were found on AA or DHA status, measured in plasma at 36 weeks gestation or in breastmilk at 6 months post‐partum (Oaks et al, ), suggesting that no such inhibition occurred. In addition, concurrent DHA status was not associated with visuospatial scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, maternal supplementation with LNS during pregnancy increased birth size, particularly among infants of first-time mothers (Adu-Afarwuah et al, 2015), and mean attained length at 18 months of age was higher among children in the comprehensive maternal and child LNS supplementation group . In the mothers, those in the LNS group were less likely to experience inadequate weight gain during pregnancy (Adu-Afarwuah et al, 2017a) and had improved essential fatty-acid status during pregnancy and postpartum (Oaks et al, 2017), and those who received LNS or MMN had improved vitamin B 12 (Shahab-Ferdows et al, 2019) and iodine status (Adu-Afarwuah et al, 2018) but did not differ in anaemia, iron status, or breast milk vitamin A concentration at 6 months postpartum or in household food insecurity, compared with those who received IFA (Adams et al, 2017;Adu-Afarwuah et al, 2017b;Klevor et al, 2016).…”
Section: Key Messagesmentioning
confidence: 98%
“…Cholesterol plays a key role in embryonic and fetal development as it is an essential component of the cell membrane and determines membrane fluidity and passive permeability (Champe & Harvey, ). It also plays important roles in cell proliferation and differentiation and cell‐to‐cell communication (Oaks et al, ). Cholesterol can be obtained from the diet and can be synthesized endogenously through cholesterol biosynthesis pathways.…”
Section: Introductionmentioning
confidence: 99%